Vulykhia, a new generic replacement name for Concavites Bondarenko & Minzhin 1981 (Anthozoa: Heliolitoidea) non Jeannet 1951 (Cephalopoda: Ammonitida) - Doweld, Alexander B. (Zootaxa, 2016)
The genus Concavites was established by Bondarenko & Minzhin (1981: 110) for fossil Upper Ordovician heliolitoids (Anthozoa) from Mongolian Altaj (Western and Eastern Mongolia, Central Eurasia), Kazakhstan (Northern Tien Shan) and Australia (Gondwana). However, the name is preoccupied by Concavites Jeannet (1951: 34), a fossil ammonite (Cephalopoda: Ammonitida: Oppeliidae), in current use (Arkell & al. 1957).